2013
DOI: 10.1073/pnas.1222166110
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TEX101, regulated by ACE, is essential for the production of fertile mouse spermatozoa

Abstract: Formation of spermatozoa of normal shape, number, and motility is insufficient for the male siring of pups. The spermatozoa must be accompanied by sound fertilizing ability. We found that males with disrupted testis-expressed gene 101 (Tex101) produce normal-looking but fertilization-incompetent spermatozoa, which were accompanied by a deficiency of a disintegrin and metallopeptidase domain 3 (ADAM3) on sperm plasma membrane. It was also found that the existence of TEX101 on spermatozoa was regulated by angiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
158
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(173 citation statements)
references
References 29 publications
(45 reference statements)
8
158
1
1
Order By: Relevance
“…According to the Human Protein Atlas, TEX101 expression is restricted to testicular tissue and male germ cells, with no evidence of expression in any other human tissue or cell type (6). Investigation of the function of mouse TEX101 demonstrated its direct role in fertilization (7)(8)(9).…”
mentioning
confidence: 99%
“…According to the Human Protein Atlas, TEX101 expression is restricted to testicular tissue and male germ cells, with no evidence of expression in any other human tissue or cell type (6). Investigation of the function of mouse TEX101 demonstrated its direct role in fertilization (7)(8)(9).…”
mentioning
confidence: 99%
“…On the other hand, downregulation of other germ cell-associated proteins may impair germline integrity and sperm-egg interaction. Downregulation of TEX101 on spermatozoa may lead to the production of fertile spermatozoa (Fujihara et al, 2013). RBMX is a regulator for maintenance and centromeric protection of sister chromatid cohesion during meiosis and depletion of RBMX by RNA interference causes the loss of cohesin from the centromeric regions before anaphase, resulting in premature chromatid separation accompanied by delocalization of the shugoshin complex and outer kinetochore proteins (Matsunaga et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The GPI-AP complex consisting of TEX101 and LY6K interacts with testicular ADAM3 and is required for sperm-fertilizing ability in mice ( 6,89 ). ADAM3 is absent from the Triton X-114 detergent-enriched phase of Ace KO spermatozoa ( 84 ).…”
Section: Gpi-anchor Cleavage Of Reck By Glycerophosphodiesterase 2 Inmentioning
confidence: 99%
“…These fi ndings raised the possibility that removal of the TEX101/LY6K complex is mediated by ACE's GPIase activity, which could reasonably explain the link between GPI-APs and ADAM3. In vitro analysis in a HEK293T culture system showed that TEX101, not LY6K, is the specifi c substrate for ACE and that dipeptidase-defective ACE retains its GPIase activity ( 6,7,89 ) ( Table 1 ). These fi ndings are consistent with the aberrant persistence of the TEX101/LY6K complex on spermatozoa in Ace KO mice.…”
Section: Gpi-anchor Cleavage Of Reck By Glycerophosphodiesterase 2 Inmentioning
confidence: 99%
See 1 more Smart Citation